Biomechanical Impact of Vertebral Augmentation Techniques: Clinical and Radiological Results in the Literature - Eliodoro Faiella; Federica Vaccarino; Domiziana Santucci; Elva Vergantino; Bruno Beomonte Zobel; Rosario Francesco Grasso (Applied Sciences)
Vertebral augmentation techniques have advanced significantly, offering improved outcomes in the treatment of vertebral compression fractures. This review explores third-generation devices such as the SpineJack®, Vertebral Body Stenting System® (VBS), and OsseoFix®, which offer enhanced vertebral height restoration, stability, and reduced complications. These devices have been shown to outperform traditional methods like vertebroplasty and balloon kyphoplasty, particularly in reducing the risk of cement leakage and ensuring long-term vertebral stability. Biomechanical studies confirm the efficacy of these systems in promoting spinal recovery. Many of these studies have utilized indirect parameters, such as the Beck Index and kyphotic angles (α and γ) measured by the Cobb method, to evaluate improvements in vertebral deformity. Furthermore, preclinical studies indicate that third-generation devices like SpineJack® enhance vertebral height restoration and stability, with performance influenced by bone quality and implant positioning, and have demonstrated superior initial and sustained height maintenance compared to kyphoplasty. While the higher costs of third-generation systems could be justified by reduced revision rates and better patient outcomes, further research is needed to optimize patient selection and assess long-term benefits. Overall, these devices could represent a significant advancement in vertebral fracture treatment, improving clinical outcomes and biomechanical stability.